Wybrane znaleziska ceramiki o cechach warsztatowych ze starszych faz wczesnego średniowiecza z południowo-zachodniej Wielkopolski i południowo-wschodniej części ziemi Lubuskiej w świetle badań specjalistycznych - Gruszka, Bartłomiej; Kara, Michał (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2013)
The latest specialist excavations of utensil ceramics from the early Middle Ages in south-west Wielkopolska and the south-east part of Ziemia Lubuska have revealed features characteristic of craft ceramics. The features include selecting the mineral leaning admixture with respect to the fraction and type, the application of slipware, as well as a potter’s wheel. The research has been based on the results of petrographic analyses of selected utensils from the sites in Bonikowo (Wielkopolska region) as well as Połupin and Stożne (Lubuskie region). The artefacts have been dated on the basis of a thermoluminescent analysis of pieces of receptacles (Stożne) and the results of radiocarbon dating (Bonikowo, Połupin, Stożne). As for the occurrence of craft ceramics, the former stages of the Early Middle Ages (approximately 6/7th-9th centuries) are strongly contrasted with the subsequent Medieval times (10th – mid-13th centuries) when this type of utensil was non-existent.